Rumble and crash : crises of capitalism in contemporary film - Sweedler, Milo, 1963- (Albany : State University of New York Press, 2019)
Analyzes six films as allegories of capitalism's precarious state in the early twenty-first century.
Exceptions and rules: states of emergency in Children of Men -- Mapping Syriana -- Corporate murder in The Constant Gardener -- Secrets of primitive accumulation: Inside Man -- Fictitious capital and narrative spin in The Wolf of Wall Street -- The meltdown and the bailout without the recovery: Blue Jasmine -- Conclusion: allegories for the present.
Includes bibliographical references (pages 159-180) and index.
Print version record.
JSTOR
Keywords: Motion pictures -- History -- 21st century; Capitalism in motion pictures; Politics in motion pictures; Cinéma -- Histoire -- 21e siècle.; Capitalisme au cinéma.; Politique au cinéma.; PERFORMING ARTS -- Reference; Capitalism in motion pictures; Motion pictures; Politics in motion pictures; 2000-2099; History